2019
DOI: 10.1111/cen.14121
|View full text |Cite
|
Sign up to set email alerts
|

The KWAK TI‐RADS and 2015 ATA guidelines for medullary thyroid carcinoma: Combined with cell block‐assisted ultrasound‐guided thyroid fine‐needle aspiration

Abstract: Objective: To compare the value of the thyroid imaging reporting and data system proposed by Kwak (KWAK TI-RADS) and the 2015 American Thyroid Association (ATA) guidelines for diagnosis of medullary thyroid carcinoma (MTC) and papillary thyroid carcinoma (PTC). To confirm the role of cell block (CB)-assisted fine-needle aspiration (FNA) in final diagnosis of MTC. Design: Retrospective hospital-based cohort study. Patients: Ninety-three patients with 29 MTCs, 31 PTCs and 33 thyroid adenomas (TAs) who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…However, it is important to stress that this observation requires validation in further prospective and multicentre studies. Hence, to avoid misdiagnosis of MTC, I agree with the conclusion of Li et al, that cell block‐assisted FNA cytology should be performed in thyroid nodules that fall into the 4a category or low suspicion category in KWAK TI‐RADS and the ATA guidelines, respectively …”
supporting
confidence: 76%
See 1 more Smart Citation
“…However, it is important to stress that this observation requires validation in further prospective and multicentre studies. Hence, to avoid misdiagnosis of MTC, I agree with the conclusion of Li et al, that cell block‐assisted FNA cytology should be performed in thyroid nodules that fall into the 4a category or low suspicion category in KWAK TI‐RADS and the ATA guidelines, respectively …”
supporting
confidence: 76%
“…The Li retrospective study of 29 patients with MTC, 31 patients with PTC and 33 patients with follicular adenoma treated in a single centre from 2000 to 2019 focused on the clinical usefulness of the recent Thyroid Imaging Reporting and Data System proposed by Kwak et al (KWAK TI‐RADS) and 2015 ATA guidelines with the combination of cell block‐assisted and ultrasound‐guided FNA for the improved diagnosis accuracy of MTC, a novel approach previously not tested . The Li study demonstrated that certain ultrasonographic features were more common in (and therefore suggestive of) MTC than PTC . It is well known that MTC and PTC may have some overlapping sonographic features of malignancy, but in this Chinese study, MTC had some sonographic features that differed from PTC, including tumour composition (mixed cystic and solid component), echogenicity (homogeneously isoechoic or markedly hypoechoic) and shape (more rounder shape).…”
mentioning
confidence: 99%
“…Approximately 95 % of MTC correspond to nodules with an intermediate or high suspicion sonographic pattern according to the ATA classification or to nodules categories 4 and 5 of TI-RADS [12][13][14][15]. FNA is recommended for non-autonomous nodules > 1 cm with this ultrasonographic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, only patients who had nodules with two or more suspicious features (solid or predominantly solid, hypoechogenicity, microcalcifications, irregular margins, anteroposterior diameter larger than transverse diameter) were included. Using this criterion, the nodules would currently be classified as intermediate or high suspicion by ATA or TI-RADS 4 or 5 [12][13][14][15].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation